Determining youths' level of understanding of environmental concepts in the sail training environment - Kilian, Kay-Leigh (Department of Biological Sciences, 2017)
The aim of this study is to determine youths' level of understanding of selected environmental concepts measured by their verbal responses. With the hypothesis being that youth would be able to observe their environment and note differences and similarities, with a basic understanding of concepts, especially those in the school curriculum but unable to take this further by hypothesising on why differences occur which is more typical of youth of ages 15 years and above. Youth would especially struggle to hypothesise theoretical and abstract concepts as opposed to describing what they observe. It is expected that studies by Piaget will be informative with regards to the cognitive developmental stages in the youth as being categorised into either stages three ( concrete-operational) or four (formal-operational). The study involved nine youths from Christel House, Cape Town, who were selected and assessed on their understanding of four environmental concepts. The crew of the sail ship noted their responses during various lessons offered on board before proceeding with the next. The results indicated that the participating youth were able to compare two different observed scenarios as being either similar or different, but were unable to compare theoretical scenarios. Once differences or similarities were established, youth were unable to link factors to hypothesise about why these differences or similarities were occurring, even when prompted or given clues from a crewmember on board the ship. However, the participants were able to hypothesise about the effects of one variable on another when they could actively manipulate a concept to see what might happen under given conditions.